Possible dialogues between the work Pedagogy of autonomy and interdisciplinarity: reflections on the initial training of pedagogues (Olhar de Professor, 2025)
Pedagogy of Autonomy is a work that discusses the essence of the progressive educator and, in our view, in an interdisciplinary way, since it reflects on teaching knowledge that is indispensable for the training of pedagogues, which reveal the composition of attitudes guided by the emancipatory spirit for the construction of autonomy and critical-reflective knowledge, actions that resemble the exercise of interdisciplinarity. Thus, we aim to reflect, on Freire's reflections contained in Pedagogy of Autonomy, on the relationships between teaching knowledge and interdisciplinarity, in order to understand the implications of these relationships in the initial training process of pedagogues, through a qualitative study of a bibliographic and documentary nature. In this way, we demonstrate that Freirean thought is echoed by multiple interdisciplinary actions such as: contextualization, humility, reflection, love, identity, bridge, attitude, change, among others, which contribute to the realization of an equitable-just-emancipatory-transformative-autonomous didactic-pedagogical-methodological task.
Keywords: Teacher training; Interdisciplinarity; Teaching knowledge